Will the Quest for UHC be Derailed? - Susan P. Sparkes; Patrick Hoang-Vu Eozenou; David Evans; Christoph Kurowski; Joseph Kutzin; Ajay Tandon (Taylor & Francis Group, 2021)
COVID-19 has shocked all countries' economic and health systems. The combined direct health impact and the current macro-fiscal picture present real and present risks to health financing that facilitate progress toward universal health coverage (UHC). This paper lays out the health financing mechanisms through which the UHC objectives of service coverage and financial protection may be impacted. Macroeconomic, fiscal capacity, and poverty indicators and trends are analyzed in conjunction with health financing indicators to present spending scenarios. The analysis shows that falling or reduced economic growth, combined with rising poverty, is likely to lead to a fall in service use and coverage, while any observed reductions in out-of-pocket spending have to be analyzed carefully to make sure they reflect improved financial protection and not just decreased utilization of services. Potential decreases in out-of-pocket spending will likely be drive by households' financial constraints that lead to less service use. In this way, it is critical to measure and monitor both the service coverage and financial protection indicators of UHC to have a complete picture of downstream effects. The analysis of historical data, including available evidence since the start of the COVID-19 pandemic, lay the foundation for health financing-related policy options that can effectively safeguard UHC progress particularly for the poor and most vulnerable. These targeted policy options are based on documented evidence of effective country responses to previous crises as well as the overall evidence base around health financing for UHC.